Child culture as a tool for prevention and health promotion: An experience report (Research, Society and Development, 2024)
Objective: To report experiences lived by medical students during childcare consultations at UBS in Imperatriz – MA carried out with children under 1 year of age, highlighting their importance both for academic training and for the child's health. Methodology: This is a descriptive, qualitative and reflective study of the experience report type, written based on the experiences of students from the 2nd period of medicine at CEUMA University in supervised internships at the Nova Imperatriz and Santa Lúcia Basic Health Units during the month of August 2023. Results: The theory and practice related to anamnesis, physical examination and the specificities related to the care of children under 1 year of age were discussed, including guidelines that should be given regarding breastfeeding, nutritional status, growth, psychomotor development, child health card, vaccination and food introduction. All these guidelines must be passed on using clear and accessible language, in order to clarify doubts that those responsible may have. With this, the academics reported the primary role of childcare consultations as a form of prevention and health promotion and the importance of communication to make this possible. Final considerations: The childcare consultation is a suitable environment for applying the knowledge that students acquire throughout their training, for the comprehensive assessment of the child and for educating those responsible for essential care for preventing and maintaining the child's health.